Landmarks in the development of human communication. (3rd December 2021) - Ruoppolo, Giovanni; Nicastri, Maria
Abstract: Objective: Describing the evolution of human communication from its origins to our days in order to provide insights useful to guide reflexions on the modern physiopathology of communication research. Methods: A series of scientific articles and texts concerning the evolution of human communication and the relationship between human communication and culture has been revised. Results: The capacity of man to mediate symbolic representations through language has led to a revolutionary transformation from "obliged" communication, already present in nature, in a "biological independent" communication, with the opportunity of creating culture, up to the point of granting control and manipulation of biological processes. Human communication, supported in modern times by the increasingly widespread channels of diffusion, has progressively become itself an object of scientific studies, able to influence the choices of recipients considered to be passive. Conclusion: Traditional landmarks in human communication have been language acquisition, writing, reading and studies on rhetoric. At present times communication is further influenced by mass media, and new frontiers are opening, including teleconsultations, instant translations, humanoid robots naturally interacting with humans and brain computer interface: will it be the last landmark in the development of human communication?